PENGARUH INVESTMENT OPPORTUNITY SET, CORPORATE COVERNANCE, PERTUMBUHAN LABA DAN STRUKTUR MODAL TERHADAP KUALITAS LABA - indah lia puspita (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2018)
Abstract Earning is a very important information in the financial statements because it is used tomeasure the performance of the company. The purpose of this study is to determine the impact ofearning growth, firm size, capital structure, investment opportunity set and corporate governancewhich consists board of independent commissioner, managerial ownership, institutional ownershipand audit committee toward earning quality. The number of samples taken as many as 17 samplesover five years using purpossive sampling method. Technique analysis that being used was liniearregression. The result of research indicate earning growth, capital structure, investment opportunityset are significant but commisaries board, managerial ownership, institutional ownership and auditcommittee are not significant to earning quality,